2016
DOI: 10.1016/j.jmbbm.2016.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Creating a model of diseased artery damage and failure from healthy porcine aorta

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 75 publications
3
7
0
Order By: Relevance
“…previously reported that collagenase and elastase treatment of porcine aorta alters the uniaxial tension response [19]. Therefore this may provide insight into the change observed in that study.…”
Section: Relative Frequencysupporting
confidence: 57%
See 3 more Smart Citations
“…previously reported that collagenase and elastase treatment of porcine aorta alters the uniaxial tension response [19]. Therefore this may provide insight into the change observed in that study.…”
Section: Relative Frequencysupporting
confidence: 57%
“…To achieve this we used an experimental system, developed previously by the authors [19] to determine methodologies for applying loads reproducibly and analysing the response of the tissue to normal and frictional loading through non-invasive imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 available in the Supplemental Materials on the ASME Digital Collection) [21]. In the latter technique, a standard fitting procedure was performed, [22,23] and these parameters are then placed into a finite element simulation of the equibiaxial loading performed in the biaxial testing. Predicted PK1 stress components from the FE model (P FE ii Þ and the analytical solution (P calc ii ) are then utilized to find a correction vector at each time point t according to…”
Section: Constitutive Model Parameter Estimationmentioning
confidence: 99%